Randomized Controlled Trial of Psychoeducation Intervention on Sexual Health Literacy Among Adolescents at Risk of HIV in Akwa Ibom State, Nigeria - Ndidi Mercy Ofole (Sociometry Journal of Social Science, Art and Humanity, 2022)
This study evaluated the effectiveness of psychoeducation intervention in enhancing sexual health literacy (SHL) among adolescents at risk of HIV. Sixty adolescents aged 12-19 years ( X̄= 15.2) who reported low in Dilorio et al. (1993) Safe Sex Behavior Questionnaire (SSBQ) were recruited from two secondary schools in Akwa Ibom State, Nigeria, and randomly assigned to treatment and waiting-list group. The intervention group received seven sessions of group-based psychoeducation to improve their HIV/AIDS knowledge, attitude towards HTC, and behaviors related to unprotected sex, condom, and contraceptive use. Participants in the waiting-list control group were not exposed to the intervention. Results show that psychoeducation was effective in improving the participants’ SHL (F (1,59) = 7264.742, p<0.05); however, there was no interaction effect of gender on the outcome. This finding suggests that psychoeducation is a viable intervention for enhancing sexual health literacy to reduce HIV infections among adolescent cohorts.